Qualitative Analysis of Psychological Framework of Online Classes during Covid-19 Using NVIVO - V, Bhatt; S, Narula; DB, Gupta; S, Sharma; D, Sabharwal (Journal of Engineering Education Transformations, 2023)
The purpose of this paper is to present the results of a study on whether or not online teaching-learning is a viable option for ensuring the quality of education in the future. The pandemic situation has brought major challenges to the educational institutions and institutions have to ensure that learning continues uninterrupted through virtual platforms using current technologies and tools. The theoretical framework for the survey is derived from secondary sources such as research papers, newspaper articles, and magazine articles on the topic. ProQuest and EBSCO were used for this. The study combines exploratory and descriptive methods. The paper shows that the future of the online education is not sustainable; it is just a situational arrangement and soon will be replaced by the old, traditional offline pattern, if the situation allows.